Moving with the Soul: Cipari Peasant Movements for Land Rights in Indonesia - Santoso, Jarot; Mutahir, Arizal; Restuadhi, Hendri; Chusna, Aidatul (Forestry Faculty, Universitas Hasanuddin, 2024)
This research explains movements by peasants in Cipari, Cilacap, Central Java, Indonesia, in demanding their land rights. Compared with similar cases in Indonesia, efforts by Cipari peasants paid off in the end and presented a unique case of success. Cipari peasants obtained ownership rights to the land on their terms. Through an empirical case study approach, we found that the Cipari peasant movement to fight for land rights lasted for a long period of time, beginning in the post-independence era and extending through the post-collapse of Indonesia’s New Order regime. For Cipari peasants, land is not just a means of production or economic resource but also has socio-cultural value and, more importantly, embodies spiritual (religious) values. These social and cultural factors provided the main driver for Cipari peasants to persist in undertaking their resistance movement. Over a long process, Cipari peasants obtained legal title to land in the form of land certificates. We show that the Cipari peasant social and resistance movement emerged and continued to develop not solely because of political opportunities but especially due to its socio-cultural values about land.